Central Australian Aboriginal Songs and Biocultural Knowledge: Evidence from Women's Ceremonies Relating to Edible Seeds. Issue Volume 39:Issues 3(2019) (September 2019) - Curran, Georgia; Barwick, Linda; Turpin, Myfany; Walsh, Fiona; Laughren, Mary
Songs encode rich knowledge of the social and ecological worlds of Aboriginal people living in the arid interior of the Australian continent, a desert with one of the most variable rainfalls in the world. People have shaped the ecology of this region in continuous feedback loops over many generations such that there is nowadays a complex system of interdependence between cultural practices and the local ecosystems. Singing traditions are an integral part of the spiritual health of the ecosystem and the means by which biocultural knowledge is carried on over many generations and through shifting social and ecological contexts. To illustrate this, we draw on traditional women's totemic songs relating to edible seeds from the Warlpiri and Anmatyerr Aboriginal groups in Central Australia. Edible seeds, predominantly acacias and grasses, once played a major role in sustaining the populations of these desert regions. They are one of five locally named food classes. We show how songs and their performance practices interact with techniques of seed production and knowledge systems connecting people to biota, the land, and their totemic religion. Traditional songs carry forward biocultural knowledge; yet, these songs and knowledge are under increasing threat because few contexts exist for their continued performance as mass media and new musical genres (e.g., country, pop, gospel) take center stage across Central Australia.